A Versatile Organic Salt Modified SnO2 Electron Transport Layer for High‐Performance Perovskite Solar Cells. Issue 16 (26th July 2021) - Peng, Xian; Zhao, Shuangshuang; Zhou, Ruonan; Gong, Xiaoli; Luo, Huxin; Ouyang, Yukun; Liu, Xingchong; Li, Haimin; Wang, Hanyu; Zhuang, Jia
Abstract: Interface engineering has been demonstrated to be effective in suppressing the defect‐related carrier recombination loss and optimizing the energy level between SnO2 electron transport layer and mixed‐cation perovskite to further improve the performance of perovskite solar cells (PSCs). Herein, a versatile organic salt, trigonelline hydrochloride (TH), is selected to modify the SnO2 /perovskite interface. TH molecule plays a multifunctional role at the interface: (1) COOH and pyridine cation can passivate the interface defects by esterification and electrostatic interaction, respectively. (2) Cl − plays a vital part in the improvement of perovskite crystallization. (3) Dipole effect can move the energy level of SnO2 resulting in optimized band alignment to more efficient electron extraction. The effects of TH at the interface are revealed by density functional theory calculations, surface chemical analyses, and energy level investigations. As a consequence, the PSCs with TH‐modified SnO2 (SnO2 ‐TH) exhibit best power conversion efficiency of 21.23%, compared to 19.59% for the reference devices, which mainly results from an enhanced open‐circuit voltage ( V oc ) from 1.098 V to 1.145 V. Moreover, the humidity stability of the non‐encapsulated devices is also significantly improved after introducing TH to the interface. Abstract : Trigonelline hydrochloride (TH) is selected to modify the SnO2 /perovskite interface. Due to the multifunctional role of TH at the interface, the power conversion efficiency of the device is increased from 19.59% to 21.23%. Moreover, the humidity stability of the non‐encapsulated device is also significantly improved after introducing TH to the interface.